Low frequency steganography algorithm for H.264/AVC - Guang-lu HUA; Zhi-tang LI; Bing FENG (Tongxin xuebao)
On the basis of analyzing some existing video data hiding algorithms and combining it with the features of H.264/AVC video low frequency coefficients,a new data hiding algorithm based on H.264/AVC low frequency domain was proposed.After quantification of DCT blocks in the low frequency area,three maximum absolute value of the nonzero coefficients were selected and information was embedded with an improved matrix encoding method.Simulation results show that the proposed algorithm can realize real-time embedding and extracting information,great capacity of embedding information,embedded high efficiency and less influence on video quality etc.